Tingkat religiusitas, pengetahuan produk, dan sikap konsumen terhadap pembelian makanan dan minuman halal - Hakim, Lukman; Waluyo, Agus (Journal of Halal Industry Studies, 2023)
This research aims to determine and analyze the influence of religiosity, product knowledge and consumer attitudes on purchasing decisions for food and drinks with halal labels as intervening variables, a study of consumers using the Tokopedia application in Salatiga. This research uses a type of quantitative research obtained through a questionnaire given to Tokopedia application users in Salatiga. The sample of this research was 100 respondents using purposive random sampling technique. The data analysis method used in this research is path analysis. The research results show that religiosity, product knowledge and consumer attitudes have a significant positive effect on purchasing decisions. Religiosity and product knowledge have a positive effect on the halal label. Meanwhile, consumer attitudes do not influence the halal label. The halal label has a positive influence on purchasing decisions. Religiosity and product knowledge have a significant positive effect on purchasing decisions through the halal label. Meanwhile, consumer attitudes have no influence on purchasing decisions through halal labels.